2013
DOI: 10.1371/journal.pone.0071892
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Suitable Reference Genes for Expression Studies in Different Pilocarpine-Induced Models of Mesial Temporal Lobe Epilepsy

Abstract: It is well recognized that the reference gene in a RT-qPCR should be properly validated to ensure that gene expression is unaffected by the experimental condition. We investigated eight potential reference genes in two different pilocarpine PILO-models of mesial temporal lobe epilepsy (MTLE) performing a stability expression analysis using geNorm, NormFinder and BestKepeer softwares. Then, as a validation strategy, we conducted a relative expression analysis of the Gfap gene. Our results indicate that in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
(46 reference statements)
2
31
0
Order By: Relevance
“…In differential gene expression studies, two types of variation can affect the results: i) biological variation among individuals, such as age, gender, ethnicity, body mass index (BMI), lifestyle, and other individual characteristics [ 10 14 ]; ii) technical variation due to sample processing, such as pipetting errors, reverse transcription efficiency, RNA quality and other [ 15 , 16 ]. Several strategies can be adopted to minimize these factors, including the use of numerous biological replicates in matched-pairs design for biological variances and the use of suitable normalizers for technical variations [ 17 20 ]. Recognition of these confounding effects is, therefore, essential for a robust experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…In differential gene expression studies, two types of variation can affect the results: i) biological variation among individuals, such as age, gender, ethnicity, body mass index (BMI), lifestyle, and other individual characteristics [ 10 14 ]; ii) technical variation due to sample processing, such as pipetting errors, reverse transcription efficiency, RNA quality and other [ 15 , 16 ]. Several strategies can be adopted to minimize these factors, including the use of numerous biological replicates in matched-pairs design for biological variances and the use of suitable normalizers for technical variations [ 17 20 ]. Recognition of these confounding effects is, therefore, essential for a robust experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the present study is that we did not evaluate potential reference genes in other epilepsy models (e.g., pilocarpine or intra‐amygdala kainate), in other strains, or in other model organisms. Previous studies have, however, validated some of the same reference genes both in human epilepsy samples (Wierschke et al, ) and in the pilocarpine rat model of epilepsy using male Wistar rats (Marques et al, ). Regarding the former, TBP, ACTB , and UBC were found to be suitable reference genes in human samples; we show here that they are appropriate for use in the 8‐hr and 30‐min PPS models.…”
Section: Discussionmentioning
confidence: 99%
“…The same study showed ACTB and GAPDH to be stable reference genes; these were ranked first in the KaL epileptogenesis and chronic epilepsy groups, respectively (Figure 1, Panel C and D). Marques and colleagues also found RPLP1 to be another stable reference gene in the pilocarpine model (Marques et al, 2013); it was ranked among the top four for both the 30-min PPS and chronic KaL groups (Figure 1, Panel B and D).…”
mentioning
confidence: 89%
“…3F) in chronic period may reflect the first step of a process in which seizures induce astrocytic hypertrophy and may be also related with brain damage. Changes in astrocytes can modify the homeostasis in the extracellular microenvironment contributing to the development of an epileptic state (Chen et al, 2013;Marques et al, 2013;Steward et al, 1992). The decline of EAAT2 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%